Shaking-table tests and numerical simulations on a subway structure in soft soil. Issue 76 (September 2015) - Guoxing, Chen; Su, Chen; Xi, Zuo; Xiuli, Du; Chengzhi, QI; Zhihua, Wang
Abstract: Shaking table tests were performed to investigate the damage mechanisms of a subway structure in soft soil while experiencing strong ground motions. The seismic responses of the structure and soil were found to be more sensitive to input motions with richer low-frequency components. The excess pore pressure ratio of soil increased slightly, and the distribution of the excess pore pressure surrounding the structure showed clear spatial effects. The frequency spectrum characteristics of input ground motions clearly influenced the lateral displacement of the structure. In addition, the structure was most severely damaged at the top or the bottom of the interior columns. Finite element analyses were conducted by using the modified Martin–Seed–Davidenkov viscoelastic and the rate-independent plastic-damage constitutive models for soil and concrete, respectively. Satisfactory agreement was observed between the simulation and test results, the difference between these results was discussed in detail. The results provide insight into how the characteristics of strong ground motion might influence and present a simplified analysis method to quantitatively evaluate the damage of subway structures in soft soil. Highlights: Study of damage mechanisms of soft soil subway structure under strong ground motions. Seismic response more sensitive to input strong motions with richer low-frequency components. Structure most severely damaged at the sidewall, at the top/bottom of interior columns.